ANALISIS AKUNTANSI MODAL BANK: MODAL INTI DAN MODAL PELENGKAP DALAM STRUKTUR PERBANKAN MODERN - Suwarni Nainggolan; Nopitri Zega; Irma Marpaung; Ardi Lumban Tobing; Hamonangan Siallagan (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the concept of bank capital accounting with a focus on two main components of capitalization, namely core capital (first tier capital) and supplementary capital (second tier capital). A bank’s capital structure serves as a fundamental foundation for maintaining stability, resilience, and the bank’s ability to withstand various financial risks. This research employs a descriptive qualitative approach through a literature study of academic sources, banking regulations, and international standards such as those issued by the Basel Committee. The findings indicate that core capital is the highest-quality component of capital, characterized by its permanence and strong capacity to absorb losses directly. This component consists of share capital, share premium, and retained earnings, all of which play a significant role in maintaining the bank’s financial soundness and meeting capital adequacy requirements. Meanwhile, supplementary capital functions to strengthen the bank’s overall capitalization capacity through instruments such as revaluation reserves, subordinated debt, and hybrid instruments. Although its quality is lower compared to core capital, supplementary capital remains crucial in supporting the bank’s financial flexibility and ensuring compliance with regulatory requirements. This study concludes that an optimal balance between core capital and supplementary capital is an essential capitalization strategy to ensure the bank’s operational sustainability, enhance resilience to risks, and strengthen public confidence in the banking system.